Calibrating Sap-Testing Meters - David Studstill; Eric Simonne; Robert Hochmuth; Teresa Olczyk (EDIS, 2006)
HS-1074, a 4-page illustrated fact sheet by David Studstill, Eric Simonne, Robert Hochmuth and Teresa Olczyk, provides step-by-step instructions for calibrating nitrate-nitrogen and potassium meters for use in nutrient management. Includes helpful hints, additional reading, and instructions on purchasing meters. Published by the UF Department of Horticultural Sciences, October 2006.